Financial toxicity impact on younger versus older adults with cancer in the setting of care delivery. Issue 13 (13th April 2022) - Corrigan, Kelsey L.; Fu, Shuangshuang; Chen, Ying‐Shiuan; Kaiser, Kelsey; Roth, Michael; Peterson, Susan K.; Shih, Ya‐Chen T.; Jagsi, Reshma; Giordano, Sharon H.; Volk, Robert J.; Yabroff, K. Robin; Banegas, Mathew P.; et al.
Abstract : Background: Young adults and other working‐age adults with cancer are at risk for cancer‐related financial toxicity (FT), including material hardships, depletion of coping resources, and psychological burden. This study compares FT domains in young adults (18‐39 years old) (YAs), other working‐age adults (40‐64 years old), and older adults (≥65 years old) receiving cancer care. Methods: A total of 311 adults were surveyed using the multi‐domain Economic Strain and Resilience in Cancer instrument measuring FT (0‐10 score indicating least to greatest FT; score ≥5 severe FT). Participants were receiving ambulatory care from March‐September 2019. Associations of age with overall FT and material hardship, coping resource depletion, and psychological burden FT domains were tested using Kruskal‐Wallis and χ 2 tests and multivariable generalized linear models with gamma distribution. Results: YAs (median age, 31.5 years) comprised 9.6% of the sample; other working‐age adults comprised 56.9%. Overall, material, coping, and psychological FT scores were worse in younger age adults versus older adults ( P  < .001 in all multivariable models). Compared with older adults, younger age adults demonstrated worse material hardship (median scores, 3.70 vs 4.80 vs 1.30 for YAs, other working‐age, and older adults, respectively; P  < .001), coping resource depletion (4.50 vs 3.40 vs 0.80; P  < .001), and psychological burden (6.50 vs 7.00 vs 1.00; P  < .001). Fifty percent of YAs had severe overall FT versus 40.7% of other working‐age adults and 9.6% of older adults ( P  < .001). Conclusions: Younger age adults with cancer bore disproportionate FT. Interventions to address unmet needs are critical components for addressing FT in this population. Abstract : Young adults (18‐39 years old) and other working‐age adults (40‐64 years old) with cancer experienced disproportionately greater financial toxicity compared with older adult (≥65 years old) counterparts. These younger adults faced not only severe material hardships but also severe depletion of their coping resources as well as psychological burden from their cancer‐related financial stressors.